GENETIC SELECTION FOR DOCILITY: A REVIEW - D. Norris; J.W. Ngambi; M. Mabelebele; O.J. Alabi; K. Benyi (Journal of Animal and Plant Sciences, 2014)
Animal docility or temperament is an important trait in livestock as it has influence not only on the human safety and animal welfare but importantly also on the productivity of livestock farming enterprises. Poor temperament in livestock has been associated with reduced performance, health, and carcass quality. Docility is thus increasingly becoming a focus of many studies aiming at its inclusion in animal breeding programs. Most studies on docility and its association with production have shown that the trait (docility) exhibits moderate to large additive genetic variance which could be exploited in breeding programs. Docility could potentially be used as an indicator trait for economically important traits that are difficult to measure. Techniques for measuring docility are continually being refined and improved making it possible to accurately measure docility. Identification and selection of animals with a temperament that will improve their welfare and productivity within their production environment is becoming increasingly important.
Keywords: docility; heritability; selection; temperament